Actors of the most fiendish character: Explaining the associations between the Dark Tetrad and conspiracist ideation. (March 2021) - Kay, Cameron S.
Abstract: It remains unclear why those scoring high on certain aspects of the Dark Tetrad (i.e., Machiavellianism, narcissism, psychopathy, and sadism) are more inclined to believe in conspiracy theories. The present study ( N = 474) aimed to clarify this issue by investigating the associations between the facets of the Dark Tetrad traits and conspiracist ideation in the context of five potential mediators. At least one facet of every Dark Tetrad trait was associated with conspiracist ideation, and nearly every association could be attributed, in part, to the tendency for those with aversive personalities to entertain odd beliefs, be fatalistic, and distrust others. Contrary to what the prior research might suggest, these results indicate that the conspiracist ideation found among those scoring high in the Dark Tetrad traits is the result of some shared feature of the traits rather than a feature that is unique to each trait. Highlights: Relations among the Dark Tetrad subscales and conspiracist ideation were examined. Machiavellian views and everyday sadism were associated with conspiracist ideation. Narcissistic leadership and entitlement were associated with conspiracist ideation. Psychopathic egocentricity and antisociality correlated with conspiracist ideation. Most relations were explained by odd beliefs, fatalism, and distrust.